Electrical and photoelectrical characterization of organic-inorganic heterostructures based on Ru-N-heterocyclic carbene complexes - Yaşar, Sedat; Çekirdek, Suzan; Binbay, Nil Ertekin; Tombak, Ahmet; Ocak, Yusuf Selim; Arslan, Nevin; Akin, Baysal; Aydemir, Murat; Durap, Feyyaz (OPTIK, 2018)
1,3-Bis(2-morpholinethyl)benzimidazoliumtrichlorido(eta(6)-p-cymene)-ruthenate(11), 2, was synthesized and characterized by NMR spectroscopy and micro analysis. The organic -inorganic heterojunctions were fabricated by using n-type Si wafer and a series of Ru-N-heterocyclic carbene complexes, 3-5, bearing sterically hindered aryl groups were documented for the first time. The thin films of the complexes are deposited on n-Si substrates using spin coating. Current-voltage (I-V) measurements of the devices in dark and illuminated environments were analyzed to determine electrical parameters of devices. Furthermore, the photoelectrical properties of the structures were investigated examined using I-V measurements under a solar simulator. Complexes 3 and 5 showed very low series resistance resulting in high rectification ratios which are promising results for the future electronic and photoelectronic applications. (C) 2017 Published by Elsevier GmbH.
Keywords: N-Heterocyclic carbenes; Ruthenium complex; Heterojunctions; Electrical properties